CAMPUR KODE DALAM PERISTIWA JUAL BELI DI PASAR CINA MOROSI KABUPATEN KONAWE, SULAWESI TENGGARA - Sudu, La; Lestariwati, Lestariwati; Magara, Irma; Suryati, Nurmin (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2022)
Morosi Chinese Market adjacent to PT. Virtu Dragon Nickel and PT. OSS. The employees make this market a buying and selling transaction. The Morosi Chinese Market has a very heterogeneous audience. It is also in this place that people from various places carry out buying and selling transactions, both on a large, medium and small scale. They come from various tribes and different languages so that the communication that occurs between sellers and buyers will be different, they use Chinese, Indonesian and regional languages. Buying and selling transactions in this market cannot be separated from the mixing of language codes. This study aims to explain the process of code-mixing and the forms of code-mixing that occur in the Morosi China Market. This type of research is field research using descriptive qualitative methods. Data collection is done by observing, interviewing, taking notes and recording. The results of the study show that code mixing that occurs in the Morosi China Market is in the form of code mixing in the form of root words, repeated words, and free clauses and descriptions. While the factors that cause code-mixing at the Morosi Chinese Market are due to the habits and background of the speakers, both buyers and sellers.